Comparison of Traditional Videos With Telenovelas for Hospice Family Caregivers Education. (October 2021) - Cruz-Oliver, Dulce M.; Abshire, Martha; Budhathoki, Chakra; Hladek, Melissa deCardi; Volandes, Angelo; Jorgensen, Lucas; Oliver, Debra Parker
Background: While research has shown that hospice family caregivers (HFCG) seek additional information related to patient care, pain and symptom management, and self-care, it is unknown how the use of telenovela videos for education in hospice would be received by HFCG. Objective: To explore HFCG perceived benefits and challenges with the use of telenovelas as compared to traditional educational videos during online support group. Methods: A mixed methods study with a concurrent triangulated design that analyzed qualitative interviews and YouTube analytics report to identify how viewers responded (number of views and their feedback) to telenovela videos as compared to traditional educational videos. Results: Among 39 (n = 39) HFCGs, most participants were female (80%) of White/Caucasian race, with more than high school education (85%) and they were adult children of hospice cancer patient (49%). Comparing HFCG that viewed traditional videos with HFCG that viewed telenovela videos, the telenovela video was watched more (12% longer viewing duration) and caregivers reported better content recall with informative benefits, more follow up actions and reflection about their own hospice experience. Conclusion: Caregiver feedback indicated that watching the telenovela was engaging, acceptable and produced more conversations about patient care, than watching a non-telenovela format video. Further research is needed to test telenovela efficacy in enhancing HFCG outcomes.